2014
DOI: 10.1002/pc.23219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atmospheric‐pressure air plasma discharge power on adhesive properties of aramid fibers

Abstract: After exposure to the atmospheric-pressure air plasma at different discharge powers, the adhesion characteristics of Twaron aramid fibers were investigated. For the 12 s-300 W plasma treatment, the interlaminar shear strength of Twaron fiber reinforced thermoplastic poly(phthalazinone ether sulfone ketone) was increased from 46.0 to 61.7 MPa by 34.1%, and the diffusion of water molecule into the resulting composites was proved to be effectively prevented. These results showed that surface adhesive properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…In addition, Lange et al [12] observed high increase in O content. Contrary to us, Jia et al [28] shown a decrease in O and an increase in C content. In turn, Gu et al [11] noted a decrease in O, C and N content.…”
Section: Sem/eds Analysiscontrasting
confidence: 57%
“…In addition, Lange et al [12] observed high increase in O content. Contrary to us, Jia et al [28] shown a decrease in O and an increase in C content. In turn, Gu et al [11] noted a decrease in O, C and N content.…”
Section: Sem/eds Analysiscontrasting
confidence: 57%
“…[24][25][26] Since the chopped ber surface is smooth and has less chemical reactive groups, changing the inert surface and improving surface activity of the aramid chopped ber is of great importance. 8,[27][28][29] Previous reports have made great efforts including chemical etching by mixed acids, 30 ionization, surface irradiation by plasma, [31][32][33][34] ultrasonic treatment, chemical graing methods, [35][36][37] and uorinated modication of the molecular chains 38 and other approaches. 35,[39][40][41] For instance, phosphoric acid treatment on PPTA showed increasing content of surface functional groups but resulted in a declined mechanical property of PPTA bers.…”
Section: Introductionmentioning
confidence: 99%
“…But the amounts of O and N are still much higher than that of the untreated aramid fabric. The results show that a large number of oxygen and nitrogen functional groups are introduced into the surface of aramid fabrics modified by plasma generated in this study, and the amount is much larger than that of traditional atmospheric dielectric barrier discharge in air …”
Section: Low Discharge Plasma Generation and Surface Modification Of mentioning
confidence: 81%